If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2c + -1d = 6 Solving 2c + -1d = 6 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add 'd' to each side of the equation. 2c + -1d + d = 6 + d Combine like terms: -1d + d = 0 2c + 0 = 6 + d 2c = 6 + d Divide each side by '2'. c = 3 + 0.5d Simplifying c = 3 + 0.5d
| 2x-15=-4x+27 | | 12F-4C+8C=4F+10C-3G | | 6n+6n+n-1=0 | | y=8x-25 | | 1.2p=30 | | 38+12-38+47-12+5= | | (x-2)(x+1)=7 | | K+10=6k+7 | | 11x-3+42=21x-1 | | 5d-11=16 | | 2x+5=5x+20 | | 7m+4=2m+6 | | 4(2x-3)-x=9-6(x+1) | | 10x=5/y | | X-(X*.04)=150 | | -10x+-3+-2.5+20=67 | | c=yh+x | | 2x+40-5x=1-6x+3 | | 3(3n+3)=39 | | Have-6+7h=42 | | y=3x-5-16 | | 2y-27=299 | | -2x-3x+2.5=10 | | 5+11x=-55 | | +13y-8y= | | 4x-7=38 | | 21+8x+(-15)= | | 0.72-2x=2x+x | | -0.25c+20.5=12.9 | | E/9-5=-11 | | 8x-2-4x=-12 | | E/9-5=-5 |